Punished for Strength: Sex Worker Activism and the Anti-Trafficking Movement - Rose, Ava (Atlantis, 2015)
This article is a reflection on my work as a sex worker and activist amid the global concern over human trafficking. I highlight the challenges that sex workers can experience as we attempt to position ourselves within discursive frameworks that define us by our injuries. I contend that the focus on injuries risks obscuring the varied experiences of performing sexual labour, the contributions to knowledge made by sex working people, and the solidarity within sex working communities.